RECONSTRUCTION OF THE DAILY PAID WORK AGREEMENT IN THE EMPLOYMENT LAW BASED ON JUSTICE - Christina N M Tobing; Eman Suparman; Jelly Leviza (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The directions of the establishment of Employment Law Indonesia in the era of globalization is influenced by the tendency of the existing market, labor relations aimed to the flexible work system, the indication is the legalization of the system of labor contracts / specified time work agreements (CTWA), outsourcing and daily paid workers agreement (DPWA), nevertheless in practice the flexibility of labor is still being debated in Indonesia (Agusmidah, 2011 : 359). The core existance of the flexible labor market is an attempt to change the rigid of the labor market to be more flexible and better suited to the climate of competition in the global economy that is increasingly liberal, therefore the various regulations that burden the business, deter the investment, employment and economic growth, should be abolished (Hari Nugroho and Indrasasi Tjandrasingsih, 2007 : 4). The Indonesian state concept in national development is the Welfare State, the state must realize the social welfare and also must provide protection for all citizens as a social defense. Welfare means an expectation of an objective condition where the needs for the material, spiritual, social and citizens has been fulfilled, so that they wil have decent live and able to develop themselves, be able to perform their social function as human beings as the goal to be achieved (Enam Suparman, 2015 : 3). In the specific areas of employment, welfare expentancy is formulated in the Constitution of Article 27 paragraph (2) Constitution NRI 1945, namely: "Every citizen has the right to work and a decent living for humanity" and Article 28 D (2) Constitution NRI 1945 namely : "Everyone has the right to work and to receive remuneration and fair handling and proper treatment in the employment relationship" (Eman Suparman, 2015 : 4). The form of the legal certainty is through the establishment of legislation in the field of employment that today is Law No. 13 of 2003 on Manpower. Based on the considerations of Law No. 13 In 2003, the value of the labor laws are: first, the formulation of labor law should provide protection to workers / laborers and their families in accordance with human dignity and values; second, employment law is also pay attention to the improvement of the business world. The second value must be balanced so that justice is reflected in the substance and implementation of the labor law. However the fact is that these two values are not in accordance with the aspired. This study focused on DPWA as one of the phenomena of labor flexibility, especially in the plantation sector. Palm Wacht research results, the current plantation sector employs 10.4 million workers and as many as 70% of them are workers non- guarantees job that are Freelance Workers, Labor Wholesale, Contract Labor and outsourcing ( Sawit Watch, Pers release,May 12th 2015.)  DPWA is not regulated in Law No. 13 of 2003 but included in the Ministry of Manpower and Transmigration Decree No. Kep.100 / Men / VI / 2004 on the Implementation of the Provisions CTWA. Previously there has been Regulations of the Ministry of Manpower  No. Per-06 / Men / 1985 on the Protection of Workers' Day off, in which among other provisions concerning the employer's obligation to provide the labor social security and threats penalties against violations of several articles. The regulation has been declared invalid by the Ministry of Manpower and Transmigration Decree No. : Kep.100 / Men / VI / 2004 which abolished these provisions. Ministry of Manpower and Transmigration Decree No. Kep.100 / Men / VI / 2004 solely put in 3 (three) articles about DPWA, namely Article 10 to Article 12. This provision is DPWA very flexible and does not clear to the type of work, giving rise to multiple interpretations in implementation, there is no decent wage setting, no social security employment which are the fundamental right of workers. This indicates there are discrepancy between the value of labor law with the substance of the law and its implementation, so as to give rise to injustice.  Based on the description above, it is very urgent and actual to investigate more deeply how the working relationship that is based on DPWA should be built in Employment Law so as to realize the value of labor law with the title reseach : "Reconstruction of The Daily Paid Work Agreement in the Employment Law Based on Justice”